2010
DOI: 10.1071/en10015
|View full text |Cite
|
Sign up to set email alerts
|

Cu and Pb accumulation by the marine diatom Thalassiosira weissflogii in the presence of humic acids

Abstract: Environmental context.Dissolved organic matter protects aquatic microorganisms from toxic metals by complexing and decreasing the concentration of the biologically reactive species such as free metal ions. However, there are some cases of enhancement of toxic effects when humic acids are present, which is thought to be due to effects of adsorbed humic acids on cell membranes. For a marine diatom, humic acids adsorbed to cell surfaces enhanced metal adsorption, whereas intracellular metal contents decreased as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 36 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…HA decrease Cu and Pb internalization by the algae, and this decrease is higher at higher HA concentrations. This is in accordance with the decrease in free Cu and Pb caused by complexation with HA, as measured by anodic stripping voltammetry [36]. This effect, in agreement with the free ion activity model, is supported by many other studies in the case of Cu [29,37], but contrast with the observed enhancing effect of HA on Pb uptake and toxicity to marine invertebrates [38].…”
Section: Selection Of Algae Isolation Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…HA decrease Cu and Pb internalization by the algae, and this decrease is higher at higher HA concentrations. This is in accordance with the decrease in free Cu and Pb caused by complexation with HA, as measured by anodic stripping voltammetry [36]. This effect, in agreement with the free ion activity model, is supported by many other studies in the case of Cu [29,37], but contrast with the observed enhancing effect of HA on Pb uptake and toxicity to marine invertebrates [38].…”
Section: Selection Of Algae Isolation Methodssupporting
confidence: 90%
“…It is known that HA adsorbed to cell membranes can modify membrane properties, as membrane potential or membrane permeability [39,40], and enhance the uptake of some inorganic elements, as Na þ [41], or Pb 2þ [38,40]. The fact that this enhancing effect on Pb uptake was not observed for T. weissflogii is discussed in our previous paper [36], where it is proposed that the silica frustule of the diatom protects against the adsorption of HA on the cell membrane.…”
Section: Selection Of Algae Isolation Methodsmentioning
confidence: 91%
“…The presence of colloidal material, isolated from a Swiss wastewater treatment plant effluent, also enhanced Pb uptake by C. kessleri (Worms et al 2010). In contrast, for the diatom T. weissflogii, the cellular Pb content decreased in the presence of DOM (Sanchez-Marin et al 2010a). DOM from terrestrial and riverine origin enhanced Pb toxicity for sea urchin embryos, the mussel Mytilus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of Pb by M. edulis gills was significantly lower when the exposure medium was supplemented with fulvic acid and Suwannee River DOM . In a marine diatom ( Thalassiosira weissflogii ), humic acid did not alter the amount of Pb that was internalized, although humic acid concentrations were positively related with adsorption of Pb to the exterior of the cell wall of the diatom . Nogueira et al observed that enzyme activity in embryonic Mytilus galloprovincialis was altered during 48‐h exposures to several types of natural organic matter but that the addition of metals (including Pb) did not generally alter enzyme activity beyond the effect of organic matter alone.…”
Section: Discussionmentioning
confidence: 99%